2017
DOI: 10.1159/000477262
|View full text |Cite
|
Sign up to set email alerts
|

Current Developments in Mobilization of Hematopoietic Stem and Progenitor Cells and Their Interaction with Niches in Bone Marrow

Abstract: The clinical application of hematopoietic stem and progenitor cells (HSPCs) has evolved from a highly experimental stage in the 1980s to a currently clinically established treatment for more than 20,000 patients annually who suffer from hematological malignancies and other severe diseases. Studies in numerous murine models have demonstrated that HSPCs reside in distinct niches within the bone marrow environment. Whereas transplanted HSPCs travel through the bloodstream and home to sites of hematopoiesis, HSPCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 160 publications
0
17
0
1
Order By: Relevance
“…Mesenchymal stem cells (MSCs) and endothelial cells (ECs) are the two major types of cells in bone marrow niche. It has been reported that ECs provide a nutrient-rich hematopoietic niche for HSC, which can effectively promote HSC proliferation and differentiation [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) and endothelial cells (ECs) are the two major types of cells in bone marrow niche. It has been reported that ECs provide a nutrient-rich hematopoietic niche for HSC, which can effectively promote HSC proliferation and differentiation [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, cells of the BM niche can retain BCCs in a dormant phase, making them difficult to treat. In addition, it is important to note that any treatment of BCCs within the BM microenvironment must avoid overt toxicity to the endogenous hematopoietic stem cells 27 , 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…␣4 integrin seems to play few roles in this process, with controversial expression on peripheral blood neutrophils (42)(43)(44). A wide range of studies revealed that VLA-4/VCAM-1 adhesion signaling is essential in homeostatic stem cell/progenitor cell egress from the bone marrow (45,46). Although the effect of VLA-4 on neutrophil release from the bone marrow under rest condition is debated, VLA-4 has been proven to mediate marrow neutrophil mobilization under stress conditions (17,19).…”
Section: Regulation Of ␣4 Integrin By Glutathionylationmentioning
confidence: 99%